2019
DOI: 10.1136/bcr-2018-228845
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant of Guillain-Barré syndrome after chikungunya viral fever

Abstract: Chikungunya (CHIK) viral fever is a self-limiting illness that presents with severe debilitating arthralgia, myalgia, fever and rash. Neurological complications are rare. We present a case of a 36-year-old woman who presented with acute onset progressive difficulty swallowing and left arm weakness. She was diagnosed with CHIK viral fever 4 weeks prior to admission. After investigations, she was diagnosed with a pharyngeal–cervical–brachial variant of Guillain-Barré syndrome. In hospital, she required ventilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During the Chikungunya outbreak at Reunion Island, France in 2005–2006, Lebrun et al reported 2 cases of GBS with antecedent Chikungunya infection. In both the patients, Chikungunya infection was confirmed by the presence anti-Chikungunya IgM and IgG antibodies in serum and CSF [ 45 53 ]. Antecedent Chikungunya infections in GBS reported globally in the last two decades are depicted in ( Table 1 ) .…”
Section: Literature Review: Antecedent Infections In Gbsmentioning
confidence: 99%
“…During the Chikungunya outbreak at Reunion Island, France in 2005–2006, Lebrun et al reported 2 cases of GBS with antecedent Chikungunya infection. In both the patients, Chikungunya infection was confirmed by the presence anti-Chikungunya IgM and IgG antibodies in serum and CSF [ 45 53 ]. Antecedent Chikungunya infections in GBS reported globally in the last two decades are depicted in ( Table 1 ) .…”
Section: Literature Review: Antecedent Infections In Gbsmentioning
confidence: 99%
“…GBS is often preceded by an infection with Campylobacter jejunii , mycoplasma pneumoniae , EBV, CMV, influenza-A, or hepatitis-E [ 42, 45 ]. Micro-organisms more rarely triggering GBS include scrub typhus (Tsutsugamishi fever) [ 46 ], Chikungunya [ 47 ], rubella virus [ 45 ], VZV, Toscana virus, hepatitis-C, hepatitis-A, hepatitis-B, West Nile, COVID-19, SARS-CoV-2, or Zika [ 48 ]. Rare, non-infectious triggers of GBS include hyponatriemia [ 49 ], bariatric surgery [ 50 ], lupus, pregnancy [ 42 ], or bacterial meningitis [ 51 ].…”
Section: Acquired Neuropathiesmentioning
confidence: 99%
“…The arthralgia can persist for months after the acute infection, characterizing the main chronic incapacitating symptom of those infections. However, both viruses have been associated with more severe neurological manifestations, such as meningo-encephalitis, Guillain-Barré syndrome, acute disseminated encephalomyelitis (ADEM), and severe myelitis, with increasing reports of neuro-CHIKV in endemic areas such as Brazil ( Bandeira et al., 2016 ; Balavoine et al., 2017 ; Khatri et al., 2018 ; Maria et al., 2018 ; Simon et al., 2018 ; Hameed and Khan, 2019 ; Silva et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%